Empowerment of River Flow Region Communities Based on Open Water Swimming, Dive, and Post Flood Safety Simulation in Banjar District - Eka Purnama Indah; Norma Anggara; Endang Pratiwi (Universitas PGRI Palembang, 2023)
Making PJOK learning videos is needed in helping teachers for online learning to be delivered to students. The purpose of this activity is to help PJOK teachers make basic learning videos of big ball games using video editing applications. This activity was carried out directly with the method of lectures, demonstrations, discussions and structured guidance on September 15, 2020 in Kusan Ilir District, Tanah Bumbu Regency. Participants in this activity are PJOK teachers who are recorded on duty in the 3T area as many as 8 people. Teachers who have never made simple and short learning videos using video editing applications are very excited because the videos produced using these applications can be directly shared with students. This activity received a response on very good criteria for the four aspects assessed, namely material, resource persons, duration and delivery media and the teacher can make PJOK learning videos. . The goal is to express the real meaning of playing, even though students only follow the movement through virtual videos